1972
DOI: 10.1042/bj1281285
|View full text |Cite
|
Sign up to set email alerts
|

Ring hydroxylation of di-t-butylhydroxytoluene by rat liver microsomal preparations

Abstract: 3,5-Di-t-butylhydroxytoluene (compound I) was converted into 4-hydroperoxy-4-methyl-2,6-di-t-butylcyclohexa-2,5-dienone (compound II), 4-hydroxy-4-methyl-2,6-di-t-butylcyclohexa-2,5-dienone (compound III) and 2,6-di-t-butyl-4-hydroxymethylphenol (compound IV) by rat liver microsomal preparations in the presence of NADPH and air. The oxidation of compound (I) by m-chloroperbenzoic acid also produced the same compounds. These results suggest that hydroperoxide can be an intermediate in aromatic hydroxylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…BHT is metabolized in the body through oxidations of the benzyl and tert -butyl parts to yield two distinct alcohols 22 , 23 , 24 ) . In addition, 4-hydroperoxy derivative of BHT and quinone methide are identified in vitro and these are proposed to link to the pulmonary toxicity in mice 25 , 26 ) . The formation of the peroxy-derivative is inhibited by carbon monoxide and SKF525-A, suggesting the P450-mediated production, although no data is available for human CYP enzyme(s) involved in the formation of the peroxy-derivative.…”
Section: Resultsmentioning
confidence: 99%
“…BHT is metabolized in the body through oxidations of the benzyl and tert -butyl parts to yield two distinct alcohols 22 , 23 , 24 ) . In addition, 4-hydroperoxy derivative of BHT and quinone methide are identified in vitro and these are proposed to link to the pulmonary toxicity in mice 25 , 26 ) . The formation of the peroxy-derivative is inhibited by carbon monoxide and SKF525-A, suggesting the P450-mediated production, although no data is available for human CYP enzyme(s) involved in the formation of the peroxy-derivative.…”
Section: Resultsmentioning
confidence: 99%
“…BHT undergoes biotransformational processes not only in foods, natural environments, such as air, dust, soils, or water (Fries and Püttmann , ; Fernandez‐Alvarez and others ; Rodil and others , ), but also in living organisms. The metabolism of BHT is very complex and it has been investigated in different animal species, such as rats (Daniel and Gage ; Ladomery and others ; Daniel and others ; Holder and others ; Shaw and Chen ; Matsuo and others ; Conning and Phillips ), mice (Matsuo and others ), rabbits (Dacre ; Conning and Phillips ), chickens (Frawley and others ), monkeys (Allen ; Conning and Phillips ), dogs (Gage ), and also in humans (Daniel and others , ; Holder and others ; Conning and Phillips ). As BHT undergoes several reactions during biotransformation, a large number of intermediate metabolites have been identified.…”
Section: Biotransformation Of Bhtmentioning
confidence: 99%
“…Chemical studies have identified epoxides (Grover et ~' 1971), hydroperoxides (Shaw and Chen, 1972), and other reactive compounds as possible intermediates, but so far neither these nor spectroscopic methods have succeeded in delineating the main reaction pathway. We have recently begun an extensive study of the magnetic circular dichroism (Mco 1 ) of a variety of hemoproteins and their derivatives and of some model heme compounds (Vickery; Nozawa and Sauer, in ·preparation).…”
Section: ~S-mentioning
confidence: 99%